Macroeconomic variables of AirAsia Berhad stock return / Wan Nurul Nabila Wan Zaidi - Wan Zaidi, Wan Nurul Nabila (Faculty of Business and Management, 2018)
This paper discussed the relationship of USD Exchange Rate, Crude Oil Price and Leverage towards Stock Return of AirAsia Berhad. The period of study is from 1st Quarter of 2005 until 4th Quarter of 2016 which consists of 12 years. Time series data is used in this study. Several test run on the data to ensure that the model developed and the result produced would be reliable. All the variables used in this study passed all the test. Multiple Linear Regression analysis is used in determining the relationship between variables in this study. In conclusion, this study revealed that there is insignificant relationship of USD Exchange Rate and Leverage towards Stock Return of AirAsia Berhad. Meanwhile, there is significant and positive relationship between Crude Oil Price and Stock Return of AirAsia Berhad.